THE PREVALENCE OF ORAL MUCOSA LESIONS IN PEDIATRIC PATIENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Lesions of the oral mucosa are a broad range of different alterations located in the soft tissue of the oral cavity. The studies that desribe the prevalence of oral mucosal lesions have been carried out mainly in a adult population. The prevalence of oral mucosa lesions (OMLs) among children varies from 4.1% up to 69.5%. There is a lack of sufficient epidemiological data and adequate knowledge about OMLs in relation to minors’ gender and age. The aim of the study was to evaluate the prevalence of OMLs in children, patients of the oral pathology clinic in south-western parts of Poland, and to investigate the potential correlation between the occurrence of particular types of OMLs and the gender and age. A retrospective study was performed using a total of 2474 clinical charts from 2015 to 2019. Data collected included age, gender, and OMLs’ type. The prevalence of OMLs in minors was 5.21%. Aphthae was the most frequent diagnosis. Boys were more commonly affected, and traumatic erosion and ulcers were significantly more often detected in males.